To Shoot Or Not To Shoot? Southeast Asian And Middle Eastern Militaries Respond Differently - James M. Dorsey (2016)
An analysis of the Middle Eastern and North African militaries has produced a laundry list of literature, much of which was either valid for a specific post-World War II period or highlighted one of more aspects of military interest in the status quo or attitudes towards political change. Leaving aside the geopolitical differences between Southeast Asia and the Middle East and North Africa, a comparison of the transition in both regions brings into focus the building blocks that are needed for an armed force to embrace change. Southeast Asian nations succeeded whereas the countries in Middle East and North Africa, with the exception of Tunisia, have failed for several reasons. Part of this working paper will be published in 2016 by Palgrave in 'Lost in Transition, Comparative Political Transitions in Southeast Asia and the Middle East' by Teresita Cruz- Del Rosario and James M. Dorsey.